Simulation of competition in NGNs with a game theory model - Pereira, João Paulo (2018)
Like in a real competitive market situation, Next Generation Networks (NGN) competitors need to adapt their strategy to face/react the strategies from other players. To better understand the effects of interaction between different players, we build a Game Theory model, in which the profit of each operator will be dependent not only on their actions, but also on the actions of the other operators in the market. This paper analyzes the impact of the price (retail and wholesale) variations on several output results: players’ profit, consumer surplus, welfare, costs and service adoption. We assume that two competing FTTH networks (incumbent operator and new entrant) are deployed in two different areas. We also propose an adoption model use in a way that reflects the competition between players and that the variation of the services prices of one player has an influence on the market share of all players. Finally, model use the Nash equilibrium to find the best strategies.